ANALISIS KEMAMPUAN DAN KEANDALAN MESIN BUBUT WEILER PRIMUS MELALUI PENGUJIAN KARAKTERISTIK STATIK MENURUT STANDAR ISO 1708 - Rendy Revo Runtu; Jan Soukotta; Rudy Poeng (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2015)
The aim of this research is to determine the operational feasibility of machine’s tool by testing the characteristic of static geometric based on ISO-1708 standard. The object is Weiler Primus lathe located in Sam Ratulangi (Unsrat) engineering manufacturing laboratory. Examination covered five measurements, which is harmonization to the machine base and sledge, motion alignment head move off relatively against the sledge movement, accuracy of the main spindle, alignment of rote launcher axis fuse and the axle carrier’s accuracy due to keming in the bearing press. Measurement of the five tests were done because of the limitation of measuring tools which can support the other measurements. The result of deviation value obtained from the test will be compared with allowed deviation value based on ISO-1708 standard. The measurement result of the five types of tests shows that Weiler Primus’s lathe located in Unsrat engineering laboratory is conform with ISO 1708 standard. In other words, the late posses the ability and reliability to produce a product or tool with high accuracy with an average reliability of 99,370%. Keywords: Geometric Accuracy, Machine Tool’s. Lathe